Intangible assets as a source of competitiveness of real-estate developers - Justyna Grześ-Bukłaho (Ekonomia i Prawo, 2018)
Motivation: resources of an enterprise are understood widely and include both tangible means as well as immaterial assets. Currently, there is an increasing emphasis on the importance of intangible resources in building the competitive advantage of an enterprise. Competitive advantage is identified with the status desired by an enterprise, which operates in a competitive environment. It can be defined as a disproportion among enterprises, which allows one company to compete better than others on the market. The purpose of the analysis is usually therefore to determine the sources of competitive advantage. The knowledge is particularly important for enterprises operating in the property development sector, which is characterized by a considerable volatility resulting from changes in the economic situation in the whole construction sector. Aim: the purpose of the article is to answer the question of what factors are important in the process of building a competitive advantage of real-estate developers, in particular, what is the role of intangible resources. Results: conclusions of the analysis made it possible to formulate a summary of intangible assets that contribute most to building a competitive advantage of real-estate developers. These factors were included in several areas, inter alia: enterprise market, relations, finances, product, human resources.